(untitled) (Materiali di Estetica. Terza serie, 2016)
In my paper I address Guido Davide Neri’s reading of Panofsky’s art theory formulated in his German works. I particularly focus on the critical objections raised by Neri in his introduction to the Italian anthology of Panofsky’s essays La prospettiva come “forma simbolica” e altri scritti, that he edited in 1961. In this text Neri rejects a dualistic rigid opposition of natural physiology of vision and cultural stylistic representation, as supported by the neo-Kantian Panofsky in his seminal essays on the iconological levels, and advocates a more nuanced approach, capable of connecting sensibility and style.